Continuous tool-path planning for optimizing thermo-mechanical properties in wire-arc additive manufacturing: An evolutional method. (November 2022) - Zhou, Zeyu; Shen, Hongyao; Lin, Jiahao; Liu, Bing; Sheng, Xinjun
Abstract: Continuous tool-path is often chosen to improve deposition efficiency and forming quality in wire-arc additive manufacturing. However, the concentration of adjacent tool-path fragments makes the thermo-mechanical properties of continuous tool-paths tend to be poor, resulting in performance degradation and other defects. This work focuses on the efficient planning of the continuous tool-path with fine thermo-mechanical properties and proposes an evolutional method based on genetic algorithm. All the key operations of the proposed method, such as crossover and mutation, are designed based on the characteristics of the research object. Thereinto, the fitness of a continuous tool-path is evaluated within several seconds by using the rapid thermo-mechanical field prediction model, which ensures the efficiency of the whole planning process. Additionally, the formability constraint is introduced to ensure the forming quality of the part fabricated with the planned tool-path. The experiments demonstrated that the thermo-mechanical properties of the planned tool-path improves by more than 87 % and the average residual Von Mises stresses of it decreases by more than 32 MPa. Meanwhile, the time cost of a single planning process is at the hour level, which is acceptable when considering that it takes several hours for the numerical simulation method to calculate one thermo-mechanical field. Graphical abstract: Unlabelled Image